2021
DOI: 10.31138/mjr.32.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of the ABO Blood Type in Patients with Rheumatic Diseases: Is there a Link to the ABO and Rhesus?

Abstract: Objectives: Several studies have shown associations of ABO and Rh blood groups with various diseases; however, the relationship of ABO and Rh blood groups with rheumatic diseases are scarce. The aim of the present study was to examine whether there is an association between ABO and Rh blood groups and the types of rheumatic diseases. Method: In this multi-centre cross-sectional study, sociodemographic data, type of rheumatic disease, and type ABO and Rh blood groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…35 In addition, a study by Salem et al performed in Egypt showed that blood type A is more common in patients with rheumatic disease. 4 We also found no significant association between Rh blood group and T2DM (OR ¼ 0.91, 95% CI: 0.78-1.06), as previously shown in studies conducted in India, 22 Algeria, 36 and Ethiopia. 14 However, a study by Stern et al showed a statistically significant association between T2DM and Rh blood type.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…35 In addition, a study by Salem et al performed in Egypt showed that blood type A is more common in patients with rheumatic disease. 4 We also found no significant association between Rh blood group and T2DM (OR ¼ 0.91, 95% CI: 0.78-1.06), as previously shown in studies conducted in India, 22 Algeria, 36 and Ethiopia. 14 However, a study by Stern et al showed a statistically significant association between T2DM and Rh blood type.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the study by Salem et al showed that Rh-positivity is more common in patients with rheumatic disease. 4 In contrast, a study conducted in Pakistan 27 showed that Rh-negativity is significantly associated with T2DM. A possible explanation for this is that the Rh blood system may be linked to glucose metabolism, and thereby affect the clinical manifestation of diabetes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…15 We also found a novel shared gene, ADAM15, whose expression serves as an adhesion receptor for platelets, plays a role in platelet activation and thrombus formation. 29 Hematological alterations are also common in patients with SLE, 30,31 these evidence suggests the important function of erythrocyte surface antigens and coagulation in COVID-19 and SLE co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between ABO blood group and the occurrence and prognosis of chronic inflammatory diseases, such as inflammatory bowel disease and autoimmune diseases have been reported. [60][61][62][63][64][65][66][67][68][69][70][71][72] Chronic inflammation is related to tumor growth, invasion, and migration. [34][35][36] Therefore, we speculate that these inflammatory mediators directly correlate ABO blood groups with tumor development and spread.…”
Section: Dovepressmentioning
confidence: 99%